The Polyhomeotic protein induces hyperplastic tissue overgrowth through the activation of the JAK/STAT pathway. - González, I.; Simón, R.; Busturia, A. (Cell Cycle, 2009)
Epigenetic mechanisms controlling cellular proliferation are essential to animal development. Moreover, altered levels of expression of the epigenetic regulator proteins are associated with the development and progression of human diseases like cancer. We have studied the effects of high levels of Polyhomeotic (PH) protein, a member of the Polycomb Group (PcG), during the proliferation of the imaginal discs in Drosophila. Overexpression of PH protein causes induction of proliferation, accompanied with induction of JNK-dependent apoptosis. As a result, massive hyperplastic overgrowth is produced and the corresponding differentiated tissues show phenotypes related with mis-regulation of homeotic gene expression. We have found that high levels of PH upregulate the JAK/STAT pathway through the de-repression of Unpaired (UPD), the extracellular ligand of the Drosophila JAK/STAT signalling cascade. Moreover, inactivation of the JAK/STAT pathway in the presence of a large amount of PH protein greatly reduces the tissue overgrowth, demonstrating a functional role of JAK/STAT in PH-induced hyperplasia. Finally, we have observed that decapentaplegic and d-myc, two growth genes and putative targets of the JAK/STAT pathway, are also overexpressed in the PH-induced tumors. We propose that during normal development, the PcG proteins act to maintain inactive the JAK/STAT pathway. Upon cellular stress, changes in the levels of PcG proteins expression are induced and JAK/STAT is activated leading to tumor development. Our results show a functional relationship between the PcG gene expression and the JAK/STAT pathway, both of which are found to be perturbed in tumorigenesis.